Keeping children safe at home: protocol for a case–control study of modifiable risk factors for scalds. Issue 5 (19th May 2014) - Wynn, P; Stewart, J; Kumar, A; Clacy, R; Coffey, F; Cooper, N; Coupland, C; Deave, T; Hayes, M; McColl, E; Reading, R; Sutton, A; et al.
Abstract : Background: Scalds are one of the most common forms of thermal injury in young children worldwide. Childhood scald injuries, which mostly occur in the home, result in substantial health service use and considerable morbidity and mortality. There is little research on effective interventions to prevent scald injuries in young children. Objectives: To determine the relationship between a range of modifiable risk factors for medically attended scalds in children under the age of 5 years. Design: A multicentre case-control study in UK hospitals and minor injury units with parallel home observation to validate parental reported exposures. Cases will be 0–4 years old with a medically attended scald injury which occurred in their home or garden, matched on gender and age with community controls. An additional control group will comprise unmatched hospital controls drawn from children aged 0–4 years attending the same hospitals and minor injury units for other types of injury. Conditional logistic regression will be used for the analysis of cases and matched controls, and unconditional logistic regression for the analysis of cases and unmatched controls to estimate ORs and 95% CI, adjusted and unadjusted for confounding variables. Main exposure measures: Use of safety equipment and safety practices for scald prevention and scald hazards. Discussion: This large case-control study will investigate modifiable risk factors for scalds injuries, adjust for potential confounders and validate measures of exposure. Its findings will enhance the evidence base for prevention of scalds injuries in young children.